Impact of resistance exercise variants on sarcopenia: a scoping review - Stuti Sharma; Mahak Sharma; Divya Tripathi; Gulshan Lal Khanna (Discover Public Health)
Abstract Background Sarcopenia is defined as a condition that is well explained as the muscle loss associated with old age, which can evolve into increased fall risk and decreased physical capabilities, decreasing the quality of life. Exercise intervention is important for the reversal or prevention of this muscle loss. Objective The study aimed to find out the influence of resistance exercise on Sarcopenia. Methods A systematic database search was conducted for randomised controlled trials, community-based trials, and clinical trials. “Sarcopenia” and “Exercise”, “Sarcopenia” and “Resistance Training”, “Sarcopenia” and “Randomized Controlled Trials”, and “Sarcopenia” and “Clinical Trials” search terms were used on the PubMed database and Cochrane database, and relevant articles were incorporated into the study. Results This review analyzed 35 research studies, all of which centered on using resistance exercise interventions to improve sarcopenia. Among the studies analyzed, diverse cohorts were observed, comprising nutrition, control, and exercise groups.Resistance exercise with combination of balance or postural training showed a positive impact, in reduction of indicating the importance of balance in reducing the risk of falls and proved most beneficial in the progression of Fat-Free Mass, on the other hand Resistance Exercise with Weights proved to be most beneficial in improving Strength but the differences were not statistically significant. Resistance exercise, when performed with a high-protein diet, has shown higher efficacy in the reversal of sarcopenia by decreasing the risk of falls and fractures, but inter-variant differences did not reach statistical significance. Conclusion Overall, this review indicates that resistance exercise, when performed consistently for more than 16 weeks combined with dietary intervention, might have a beneficial effect on the reduction of sarcopenia. More studies need to be conducted with a long study duration to analyze the real effect of resistance exercise on sarcopenia.